The effects of fertility on female labor supply - Nguyen Thi Hong, Thoan (Kansas State University, 2009)
This report reviews the effects of fertility on female labor supply, primarily female labor force participation and work hours. Although estimates of the causal relationship between fertility and female labor supply are mixed, this report tries to review why and by how much an additional child in a family affects work decisions and work hours of mothers on average. Statistical analysis shows a decreasing trend in fertility and an increasing trend in female labor force participation throughout the world over the last four decades. Using different specifications and estimation techniques, empirical studies suggest that fertility has negative effects on maternal labor supply because childbearing falls on women and women have lower wage rates than men on average. The negative relationship between fertility and female labor supply is explained by social, economic, and technical forces that affect fertility and female labor supply, including an increase in the value of women’s time due to an increase in education levels of women, expensive childcare, and substitutes for children; emphasis on quality instead of quantity of children; an increase in employment opportunities for women; changes in social norms towards supporting women working outside their home; and technical progress in birth control.
Keywords: Fertility; Female labor supply; Economics, General (0501)